Angiographic Insights and Endovascular Intervention in Pulmonary Artery Pseudoaneurysms: A Comprehensive Clinical and Pictorial Essay - Min Jeong Choi; Bong Man Kim; Sang Yoon Kim; You Me Kim (Journal of the Korean Society of Radiology)
Pulmonary artery pseudoaneurysms (PAPs) are rare and can occasionally be overlooked as a cause of hemoptysis. The rupture of PAPs may lead to severe and massive hemoptysis and asphyxiation, necessitating prompt and accurate diagnostic measures, including CT angiography, in conjunction with clinical awareness for adequate management. The aim of this pictorial essay is to establish a strategy for endovascular intervention based on a comprehensive understanding of the etiology and hemodynamics of bronchopulmonary circulation for effective and rapid PAP treatment.